Zakat Pertanian Padi Untuk Usaha Produktif (Studi Kasus Masyarkat Desa Muktijaya Kecamatan Muara Telang Kabupaten Banyuasin) - Pamuji Pamuji (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2022)
Agricultural zakat is zakat issued from agricultural products cultivated by farmers from the results of working on their fields or gardens. By increasing productive businesses through zakat where the assets or zakat funds given to mustahik are not spent, but are developed and used to help their businesses, so that with these efforts they can meet the needs of life continuously. Zakat is one of the pillars of Islam that must be carried out when someone has fulfilled the mandatory zakat requirements. In practice, zakat is worship that has a strategic position as a form of effort to develop human welfare. Correct implementation is certainly very helpful, especially in economic recovery. Muktijaya Village is a village where 80% of the people work as farmers with the majority being Muslim. Most of them make rice farming their main job. The results they get on average exceed the nisab of zakat in general. In this case, of course, the people of Muktijaya Village cannot be separated from the implementation of zakat on rice farming. The majority of rice farmers there distribute their zakat directly to their relatives and neighbors who they consider to be people in need. give all zakat assets to one of the mustahik groups (people who are entitled to receive zakat), this they do to facilitate the process of distributing zakat. The amil zakat institution in the village or sub-district is still not optimal, the Muktijaya village community still uses directly what the lecturers, local kyai, have conveyed.